2002
DOI: 10.1016/s0375-9474(02)01006-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonmesonic weak decay of light hypernuclei with coherent Σ mixing

Abstract: Nonmesonic weak decays of the A = 4, and 5 hypernuclei are studied. The short range parts of the hyperon-nucleon weak interactions are described by the direct quark (DQ) weak transition potential, while the longer range interactions are given by the π and K meson exchange processes. Virtual Σ mixings of the coherent type are found to give significant effects on the decay rates of 4 Λ He. A large violation of the ∆I = 1/2 rule is predicted in the J = 0 transition amplitudes. many-body dynamics and nonperturbati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 57 publications
(74 reference statements)
2
37
0
Order By: Relevance
“…This might indicate that, neither the FSI, nor the two-nucleon induced decay processes play a significant role in the s-shell, at least not for 4 Λ He. As a byproduct we have found that the π + K exchange potential with soft cutoffs (SPKE) is capable of accounting for the experimental values related to Γ p and Γ n in all three [30].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This might indicate that, neither the FSI, nor the two-nucleon induced decay processes play a significant role in the s-shell, at least not for 4 Λ He. As a byproduct we have found that the π + K exchange potential with soft cutoffs (SPKE) is capable of accounting for the experimental values related to Γ p and Γ n in all three [30].…”
mentioning
confidence: 94%
“…The most relevant issue here is, however, that there is a region of rather soft Λ π and Λ K where all the Γ N are reproduced fairly well. 2 In Table I are shown the results for Λ π = 0.7 GeV and Λ K = 0.9 GeV, labelled as P3, which we call the soft π + K exchange (SPKE) potential, and which will be used in the evaluation of the NMWD spectra We are aware that the OME models predict a too large and negative asymmetry parameter a Λ in 5 Λ He [13,21,22,23,30,32], and also that there are two recent proposals to bring this value into agreement with experiments by going beyond the OME model and incorporating [27]; T2 -(π +4BP I) [28]; T3 -(PKE) [30]; T3' -(π +K +DQ) [30]; T4 -(π + 2π/σ + 2π/ρ + ω) [14]; T5 -(PSVE) [16]; T6 -(π + K + σ + DQ) [31], T7 -(PSVE) [33]; T7' -(PSVE +2π + 2π/σ) [33]. C) Present Results: P1 -(PSVE); P2 -(PKE); P3 -(SPKE).…”
mentioning
confidence: 99%
“…In the evaluation of Γ N M , and the corresponding spectra, are used the Shell Model (SM) and the Fermi Gas Model (FGM) for Γ 1 (within the two-particle phase space) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][20][21][22][23], while for Γ 2 (within the three-particle phase space) only the later model has been employed so far [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…where Γ pp stands for the Σ + p → pp transition which is available when the virtual Σ exists (7). The Γ Y N represents the ΛΛ → Y N transition, which is a characteristic transition for the multi-Λ system.…”
Section: Introductionmentioning
confidence: 99%